2019
DOI: 10.1126/sciadv.aav0216
|View full text |Cite
|
Sign up to set email alerts
|

MRGPR-mediated activation of local mast cells clears cutaneous bacterial infection and protects against reinfection

Abstract: Selective activation of local mast cells promotes healing of bacterial skin infections and protects against reinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 51 publications
(92 reference statements)
1
92
0
Order By: Relevance
“…Poor wound healing after extensive burn, severe traumatic injury, surgery, or chronic diseases such as diabetes remains a challenging clinical problem that leads to low quality of life, substantial healthy cost, and high mortality (2,3). Open, moist, and exuding wound provides a perfect environment for bacterial colonization, and bacterial infection is recognized as a major factor that delays the healing process of wound (4,5). The host's inflammatory response is a local protective reaction in response to injury and essential for infection control in the wound sites (3).…”
Section: Introductionmentioning
confidence: 99%
“…Poor wound healing after extensive burn, severe traumatic injury, surgery, or chronic diseases such as diabetes remains a challenging clinical problem that leads to low quality of life, substantial healthy cost, and high mortality (2,3). Open, moist, and exuding wound provides a perfect environment for bacterial colonization, and bacterial infection is recognized as a major factor that delays the healing process of wound (4,5). The host's inflammatory response is a local protective reaction in response to injury and essential for infection control in the wound sites (3).…”
Section: Introductionmentioning
confidence: 99%
“…Mast cell activators can promote survival in several animal models of infection. Arifuzzaman et al found that mastoparan, a small peptide derived from wasp venom that activates mast cells through the MRGPRX2 receptor, was able to enhance clearance of Staphylococcus aureus in a mouse model of skin infection [59]. Activation of mast cells after infection was able to drive neutrophil recruitment to the site of infection, enhancing clearance of bacteria from and healing of the infected skin lesion.…”
Section: Mast Cell Activators Used To Treat Infectionmentioning
confidence: 99%
“…Wasp venom is mainly composed of a few biological active peptides (like mast cell degranulating peptides and mastoparan) (Argiolas and Pisano, 1985 ; Monteiro et al, 2009 ), active enzymes (phospholipase A2 and hyaluronidase) (Tsai et al, 2011 ), histamine, 5-hydroxytryptamine, choline, glycerin, amino acids, and so on (Schmidt, 1982 ). Among them, peptides in the wasp venom usually exhibit superior pharmacological effects and a promising clinical value (Arifuzzaman et al, 2019 ; Li et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%